M77. USE OF TESTING TO IMPROVE LONG-TERM MEMORY RECALL IN PEOPLE WITH PSYCHOSIS. (18th May 2020) - Daniel Ragland, J; Liu, Xionan; Williams, Ashley; Carter, Cameron; Niendam, Tara; Tully, Laura; Ranganath, Charan
Abstract: Background: Rather than solely assessing participant knowledge, memory tests can also facilitate long-term storage and retrieval, thereby improving episodic memory for newly studied information compared to having participants spend equal amounts of time re-studying that same information. This so called "testing effect" has been widely promoted in educational settings as a way to improve delayed recall of new information but, to our knowledge, has not been investigated as a way to improve memory in people with psychotic disorders. The goal of this study is to determine if the testing effect can be used to improve well-documented deficits in delayed recall in people with early psychosis spectrum disorders. Methods: In this within-subjects design, 20 people within 5 years of onset of a psychosis spectrum disorder (schizophrenia, schizoaffective disorder, schizophreniform disorder) and 13 demographically matched healthy controls were studied at two time points. During the first visit, a three-part 45-minute PowerPoint presentation on "what is?", "what causes?" and "how do we treat?" psychosis was presented in small group settings. After each of the 3 parts of the presentation participants were required to re-study half of the information that had just been presented and were tested on the other half of the presented information. This re-study/test procedure was repeated again a second time to promote learning and participants were instructed to return again in one week for final testing. During the second visit participants were given a final recall test on all the information included in the original presentation. Percent recall scores were examined for main effects of group, practice procedure (re-study/test) and group by procedure interactions using one-way analysis of variance (ANOVA). To account for any group differences in overall recall, a Testing Effect score was also calculated by dividing the difference in recall for information that had been tested versus restudied, by the average recall across the two conditions. Results: All participants understood the task and completed both sessions. Reflecting the overall testing effect, ANOVA revealed a main effect of task [F(1, 31)=8.2, p<.01)] with all participants showing better percent recall after one week for information that had been tested (Mean+SD=47.2 + 14.0) versus re-studied (Mean+SD=34.1 + 14.8) during their first visit. There was also a main effect of group [F(1, 31)= 8.1, p<.01], and a task by group interaction [F(1, 31)=4.3, p<.05]. To further investigate this interaction, the Testing Effect score was examined, which did not reveal any group difference [t(32)=.35, p=.73] in the percent recall improvement following testing versus re-study between patients (Mean+SD=36.6 + 45.2) and controls (Mean+SD=41.5 + 32.0). Discussion: When group differences in overall memory performance are accounted for, initial results suggest that people with psychotic disorders show the same benefit from being tested on recently studied information as do healthy participants. Simply testing patients on new information versus having them spend the same amount of time re-studying that information led to the same improvement in free recall following a one-week delay as what was seen in healthy volunteers. These results support further investigation of how the testing effect might be incorporated into cognitive remediation efforts as well as future neuroimaging studies to identify neural correlates of this positive outcome.